Sustainability framework for manufacturing in the steel industry: emphasis on eco-centric and sociocentric dimensions - Lahri, Vijay; Virmani, Naveen; Jagtap, Sandeep (Springer, 2025)
Global policies, legislation, and eco-friendly initiatives have induced the steel industry to integrate sustainable development approaches. Sustainability requires all phases from raw material sourcing to transportation to waste and carbon footprint elimination—yielding positive effects. This research employs a two-step approach in sustainability. The first phase entails conducting a systematic literature review to construct a framework identifying the sustainability key drivers, and afterwards, validating them with industry professionals. In this study, these criteria are weighted and ranked using the Best–Worst Method (BWM) within the bounds of the social and environmental aspects aimed at creating an industry tailored sustainability framework. Findings indicate that the primary ranked environmental concern is ‘E6 (Top management commitment),’ trailed by ‘E2 (Procurement of environmentally friendly raw materials)’ and ‘E4 (Technology advancement).’ Regarding social aspects, the top-ranked criteria observed as ‘S7 (Employee satisfaction) followed by ‘S6 (ISO 26000),’ and ‘S2 (Ethics).’ These results aid steel makers and policymakers remain relevant in the market by assisting the planning process of their business operational efficiencies, sustainability policies, and compliance regulations. This sustainability framework allows the steel industry to improve its competitive position by deepening the integration of social and environmental practices for enduring performance.
Keywords: Sustainability; Manufacturing firms; Social and environmental; Best-worst method; 40 Engineering; 12 Responsible Consumption and Production; 4011 Environmental engineering